Kinetic investigation on palladium-catalyzed carbonylation of allyl alcohol - Tonde, Sunil S.; Rajurkar, Kalpendra B.; Pagar, Nitin S. (International Journal of Chemical Kinetics, 2025)
Palladium-catalyzed carbonylation of allyl alcohol to 3-butenoic acid has been investigated. A significant effect of halide promoters, p-tolylsulfonic acid (TsOH), water, solvents, and PPh3 concentration activity and selectivity has been studied. Detailed kinetics of this reaction was investigated in a temperature range of 363-383 K. The influence of parameters such as stirring speed, allyl alcohol, catalyst, benzyltriethylammonium chloride (BTEAC), TsOH concentrations, and CO partial pressures on the activity and selectivity has been studied. An empirical rate equation was suggested and found to be fairly consistent with observed rate data. In addition, the activation energy and kinetic parameters were evaluated.
Keywords: allyl alcohol; Carbonylation; halide promoters; kinetics; Mechanism; Palladium